TCF7L2 rs290487 C allele aberrantly enhances hepatic gluconeogenesis through allele-specific changes in transcription and chromatin binding - Zhang, Xueyou (Aging (Albany NY), 2020)
In this study, we investigated the mechanisms underlying the altered hepatic glucose metabolism and enhanced diabetes risk in individuals with the TCF7L2 rs290487 C allele. Analysis of 195 cirrhotic patients revealed a higher insulin resistance index and incidence of hepatogenous diabetes in patients with the rs290487 C/C genotype compared to those with the C/T or T/T genotype. The in vitro experiments using targeted mutant PLC-PRF-5 cell line showed that cells with the rs290487 C/C genotype (C/C cells) had higher glucose production, lower glucose uptake, and lower TCF7L2 mRNA and protein levels than those with the C/T genotype (C/T cells). Integrated multi-omics analysis of ChIP-seq, ATAC-seq, RNA-seq, and metabolomics data showed genome-wide alterations in the DNA binding affinity of TCF7L2 in the C/C cells, including gain (e.g., PFKP and PPARGC1A) and loss (e.g., PGK1 and PGM1) of binding sites in several glucose metabolism-related genes. These allele-specific changes in transcriptional regulation lead to increased expression of gluconeogenesis-related genes (PCK1, G6PC and PPARGC1A) and their downstream metabolites (oxaloacetate and β-D-fructose 2,6-bisphosphate). These findings demonstrate that the TCF7L2 rs290487 C allele enhances gluconeogenesis through allele-specific changes in transcription and chromatin binding.